Identifikasi Biodiversitas Hutan Mangrove sebagai Potensi Ekowisata di Kelurahan Sedau Kota Singkawang - Siva Devi Azahra; Destiana Destiana; Siti Puji Lestariningsih; Yunita Magrima Anzani (JURNAL BIOS LOGOS, 2024)
Mangrove forests are ecosystems that have potential value to be developed as natural tourism objects. This study aims to analyse the potential of mangrove forests based on the ecological perspective of flora and fauna to be used as a natural tourism area. The object of this research is a mangrove forest and the resources in it located in Sedau Village, Singkawang City, West Kalimantan Province, Indonesia. Characteristics of mangrove forest flora and fauna are determined through species composition analysis while the potential of mangrove forests as nature tourism is analysed using descriptive qualitative. The composition of flora and fauna species found in the study area as a whole consists of 7 species of mangrove trees, 6 species of herpetofauna, 4 species of aves, 2 species of mammals, and 5 species of arthropods found in the mangrove forest area. Based on the analysis of mangrove forest potential, this area has the potential to be developed as an ecotourism destination.